COVID-19-related anosmia is associated with viral persistence and inflammation in human olfactory epithelium and brain infection in hamsters - de Melo, Guilherme Dias; Lazarini, Françoise; Levallois, Sylvain; Hautefort, Charlotte; Michel, Vincent; Larrous, Florence; Verillaud, Benjamin; Aparicio, Caroline; Wagner, Sebastien; Gheusi, Gilles; Kergoat, Lauriane; Kornobis, Etienne; et al. (Science translational medicine, 2021)
Whereas recent investigations have revealed viral, inflammatory, and vascular factors involved in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lung pathogenesis, the pathophysiology of neurological disorders in coronavirus disease 2019 (COVID-19) remains poorly understood. Olfactory and taste dysfunction are common in COVID-19, especially in mildly symptomatic patients. Here, we conducted a virologic, molecular, and cellular study of the olfactory neuroepithelium of seven patients with COVID-19 presenting with acute loss of smell. We report evidence that the olfactory neuroepithelium is a major site of SARS-CoV2 infection with multiple cell types, including olfactory sensory neurons, support cells, and immune cells, becoming infected. SARS-CoV-2 replication in the olfactory neuroepithelium was associated with local inflammation. Furthermore, we showed that SARS-CoV-2 induced acute anosmia and ageusia in golden Syrian hamsters, lasting as long as the virus remained in the olfactory epithelium and the olfactory bulb. Last, olfactory mucosa sampling from patients showing long-term persistence of COVID-19-associated anosmia revealed the presence of virus transcripts and of SARS-CoV-2-infected cells, together with protracted inflammation. SARS-CoV-2 persistence and associated inflammation in the olfactory neuroepithelium may account for prolonged or relapsing symptoms of COVID-19, such as loss of smell, which should be considered for optimal medical management of this disease.